Left Ventricular Function and Echocardiographic Parameters in Patients Undergoing Chemotherapy With 5‐Fluorouracil, Anthracycline, Taxotere, and Herceptin: Prospective Cohort Study - Moghadam, Alireza Abdollahi; Fazaeli, Seyed Hamed; Kamandi, Mostafa (Health science reports, 2025)
ABSTRACT Background Despite recent progress in cancer treatment, the side effects of treatment are recognized as a major source of mortality and morbidity in patients. This study was developed and conducted to evaluate the influence of chemotherapy on left ventricular function and echocardiographic and electrocardiographic parameters in patients undergoing chemotherapy with 5‐fluorouracil, anthracycline, taxotere, and herceptin. Methods This study is a prospective cohort study on patients diagnosed with cancer. After reviewing the inclusion and exclusion criteria, patients referred for treatment with 5‐fluorouracil, anthracycline, taxotere, or herceptin were randomly divided into study groups. Echocardiographic and electrocardiographic parameters such as left ventricular ejection fraction (LVEF), LV end systolic dimension (LVESD), LV end diastolic dimension (LVEDD), tricuspid annular plane systolic excursion (TAPSE), Mid RV diameter, RA volume, QRS duration, and QTc were evaluated at the beginning of the study and 6 months after starting treatment. Subsequently, the measurements were compared and analyzed. Results Overall, 80 patients undergoing chemotherapy with 5‐fluorouracil, anthracycline, taxotere, or herceptin were included in this study. LVEF and TAPSE were significantly lower after 6 months in patients treated with anthracycline and herceptin, while LV end diastolic dimension and LV end systolic dimension were higher significantly (p‐value < 0.05). In patients treated with 5‐fluorouracil and taxotere, a significant difference in TAPSE was seen after 6 months, but no significant difference was found in LVEF or other echocardiographic parameters (p‐value > 0.05). Conclusion The findings indicated that chemotherapy with anthracycline and herceptin is significantly linked to altered left ventricular function and echocardiographic measures such as LV end diastolic dimension, LV end systolic dimension, and TAPSE. However, future research with more extensive follow‐up are recommended to investigate cardiac side effects in these patients.